Digital Skills Assessment and Digital Competences Self-Assessment Among Students at the University of Split - Tomaš, Suzana; Vrdoljak, Marijana; Kalebić Jakupčević, Katija (Revija za elementarno izobraževanje, 2024)
The aim of the research was to determine the self-assessment of digital competences and assessment of skills among students of professional and university studies at the University of Split (N=466), as well as to check whether there is a significant difference between them in terms of their year of study, gender, and scientific field of study. The results showed that senior students show a higher digital skills level, and that first-year students of humanities and social studies achieve better results than senior students on the digital skills test.
Keywords: digital literacy; higher education; national curriculum